News and Democracy: Shifting Functions over Time - Michael Schudson (Cuadernos.info)
This article focuses on the relationship between journalism and democracy by examining the primary democratic functions that the journalistic trade has provided over time and the ways in which they have changed in accordance with the trends of the broader social and cultural contexts. The author identifies six core functions, which he analyzes separately and explores the different contributions the media have made in accordance with the changes experienced by the media and the possible directions for further change in the near future.